Vietnam : High Quality Education for All by 2020 - World Bank (World Bank, Washington, DC, 2017)
This study examines the changes in Vietnam's primary and secondary education over the past 20 years as well as key factors that affect such critical educational outcomes as attendance, grade attainment, and student achievement in order to derive implications for public education policy. It is divided into an analytical report and shorter overview/policy report. The study finds significant improvement in attendance, attainment, and achievement across all populations. Nonetheless, vulnerable populations (in particular the poorest and ethnic minorities) continue to fare poorly as a result of persistent, and in some cases, increasing inequalities in educational attainment and poor student achievement. Educational attainment and achievement are also shown to be complementary to a large extent. Despite the methodological limitations, evidence consistently confirms that certain characteristics of schools and teachers are significantly related to both educational outcomes. This opens the door for public policy and provides multiple (potential) policies 'entrance points' for addressing the remaining challenges. Some measures have implications for public funding, its priorities and/or efficiency, and others are more closely related to the management of public institutions. Some of the main policy implications derived from the analytical findings are re-asserting or expanding priorities for public funding through expanding support for the Fundamental School Quality Level (FSQL), and supporting full day schooling and conditional cash transfers for vulnerable groups; improving spending efficiency through better targeted fee exemptions and the strengthened application of teacher standards; and improving the management of public sector schools through higher principals' management capacity, strengthened accountability of schools to their communities and better information.